10% liquid human immunoglobulin (KIOVIG®) for immunomodulation in autoimmune disorders. (July 2016) - Nikolov, Nikolai; Reisinger, Jürgen; Schwarz, Hans P
Intravenous immunoglobulins have been used to treat autoimmune disorders (ADs) for over 50 years. The etiologies of various ADs are not fully understood and although intravenous immunoglobulin treatment has proved its immunomodulatory properties, the roles of proposed mechanisms of action also remain a matter of speculation. A systemic search of the literature regarding KIOVIG ® (Baxalta US, Inc., MA, USA) use in clinical trials on patients with ADs and a detailed review of retrieved articles revealed eight relevant publications. These articles reported KIOVIG use in multifocal motor neuropathy, chronic inflammatory demyelinating polyneuropathy, idiopathic thrombocytopenic purpura, Kawasaki disease, Guillain–Barré syndrome and other autoimmune and neurologic disorders and showed that KIOVIG is an effective, safe and well-tolerated treatment in the studied populations. Nevertheless, further studies on larger patient cohorts are needed.